An STM and Monte Carlo study of the AlF3 film growth on Cu(111) - Candia, Adriana (2015)
We report measurements of AlF3 thin film growth on Cu(1 1 1) at room temperature by means of scanning tunneling microscopy. The growth proceeds by the formation of fractal islands characterized by a very corrugated surface. Through uncovered zones and island density we determined a diffusion length of ~25 nm for the adsorbed molecules. Even with this large diffusion length the step-edges do not appear fully decorated. These experimental results are contrasted with simulations based on a limited diffusion aggregation model and Metropolis Monte Carlo. Additionally, the results of the AlF3 sub-monolayer growth on Cu(1 1 1) are compared with our previous results on Cu(1 0 0), finding that both systems show more differences than similarities. Thus, while the growth on Cu(1 0 0) shows fully decorated step-edges, on Cu(1 1 1), they present non-covered zones even at coverages as high as 0.7 monolayers. Supported on MC simulations we suggest that the qualitative difference between both faces is due to different step-edge behaviour.